Financial Performance: Diversification Strategy, Research and Development Intensity and Ownership an Empirical Study on Healthcare Industry - Anastasia Adella; Vaya Juliana Dillak (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Many studies have examined factors influencing a company's financial performance. Some previous studies, showed inconsistent results on diversification variables, research and development intensity, and the ownership structure of the dependent variable of the company's financial performance. This research aims to examine both simultaneously and partially the variables of a diversification strategy, research and development intensity, public ownership, and institutional ownership on the company's financial performance. The financial performance used in this study is profitability. This study used a sampling technique in the form of purposive sampling. The sample in the study uses healthcare sector companies. The development of the healthcare industry in Indonesia from year to year shows potential consequences. The occurrence of a pandemic indirectly made people aware of the importance of health. Therefore, the healthcare sector is considered a promising sector and plays an essential role in driving and sustaining the national economy. The data analysis technique in this research uses panel data regression on 39 observations from 2016-2021. The empirical findings show that research and development intensity and institutional ownership significantly positively affect the company's financial performance. On the other hand, the diversification strategy has a negative effect on the company's financial performance. Meanwhile, public ownership does not affect the company's financial performance.